Does modernity still matter? Evaluating the concept of multiple modernities and its alternatives - Elsje Fourie (University of Bath, Centre for Development Studies (CDS), 2010)
In recent years, the concept of multiple modernities has emerged to challenge the perceived Eurocentrism and unilinearity of traditional theories of convergence, and has led to renewed efforts to appreciate differing trajectories of contemporary political and social development. Its exponents' key argument-that forms of modernity are so varied and so contingent on culture and historical circumstance that the term itself must be spoken of in the plural-is particularly pertinent in an era where prevailing 'Western' models of development are becoming less influential.This paper seeks to provide an examination of the main principles of this approach, a synthesis of its evolution and an analysis of its strengths and shortcomings. It examines the application of the theory to the case of Indian modernity, before addressing several alternative approaches that have attempted to fill similar gaps in the literature. It concludes with some thoughts on the future and feasibility of the study of modernity itself.The paper finds that multiple modernities has been useful in widening the scope of study, and that it focuses on important questions that its rivals have not yet addressed. However, it has not yet adequately identified the 'core' of modernity itself, nor has it refuted the charge of cultural essentialism. For modernity to retain utility as a concept, it must ultimately be viewed as a single, coherent force, albeit one which is continually contested and reversible, and which has vastly differing impacts on different societies. By addressing the ways in which this force is creatively adapted and its manifestations socially constructed, multiple modernities will be able to better identify the many ways in which societies can be modern today.
Keywords: 330